Şemsettin Sami’ye ait olduğu iddia edilen Arnavutluk’a dair eser ve Arnavutluk’ta Şemsettin Sami hakkında çıkan yazılar - Fusha, Klaudio (My University, 2018)
Türk Dili ve Edebiyatı camiasının önemli isimlerinden Şemsettin Sami dil, edebiyat ve tarih çalışmalarıyla tanınmıştır. Sami, o dönemde Osmanlı İmparatorluğu idaresinde olan Arnavutluk'taki Yanya'nın Fraşeri kasabasındandır. İstanbul'da bulunduğu dönemde hem Türk dili, tarihi ve edebiyatına hizmet etmiş hem de Arnavutluk'un kurulmasında rol oynamıştır. İstanbul'daki Arnavut Cemiyeti'nin başkanlığını yürütmüş, Arnavutça'nın alfabesini hazırlamış, Arnavutluk Ne İdi, Nedir ve Ne Olacak? adlı eseriyle de Arnavutluk'un yeniden kuruluşunda yol göstermiştir.Tezde Şemsettin Sami'nin Arnavutça ve Arnavutluk'un kurulmasındaki rolü araştırılmıştır. Kaynaklarda kendisinin bu yönüne az vurgu yapılmıştır. Bu sebeple Arnavutluk Ne İdi, Nedir ve Ne Olacak? adlı eseri ve Arnavutluk'ta hakkında çıkan yazılar Türkçeye çevrilerek tahlil edilmiştir. Çalışmanın bundan sonraki Şemsettin Sami araştırmalarına faydalı olacağını düşünüyoruz.

Şemsettin Sami, as an prominent name of Turkish Language and Literature community has been known by his linguistic, literature and historical works. At that period Sami was living in a small town called Frashëri, province of Janina (or Ioannina) in Albania ruled by the Ottoman Empire administration. During his location in Istanbul he served to the Turkish language, history and literature, also had an important part in the establishment of Albania. He had prosecute the chairmanship of Albanian Community formed in Istanbul, he had prepare the Albanian alphabet and by his work titled What Is The Past, The Present and The Future of Albania? he showed the way to re-build the Albania.In this thesis is searched the foundation role of Şemsettin Sami for the Albanian language and Albania. In all of the sources there was not a lot of details of this part of him. For this reason, his book titled What Is The Past, The Present and The Future of Albania? and some writings about them are translated to Turkish and had been analyzed. We think that the work will be beneficial for researches about Şemsettin Sami.
Keywords: 19. yy; 19th century; Albenia; Arnavutluk; Authors, Turkish; Basın; Criticism and interpretation; Eleştiri ve yorum; Political and social views; Press; Sami Frashëri; Siyasal ve sosyal görüşler; Şemseddin Sami; Şemseddin Sami, 1850-1904; Şemsettin Sami; Şemsettin Sami Hakkında Arnavutluk’ta Çıkan Yazılar; Şemsettin Sami’ye Ait Olduğu İddia Edilen Eser; Turkey; Türkiye; Work Alleged to Şemsettin Sami About Albania; Writings Published in Albania About Şemsettin Sami; Yazarlar, Türk